1995
DOI: 10.1093/hmg/4.8.1259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the positional cloning methods used to isolate the BRCA1 gene

Abstract: A critical step in positional cloning is the identification of candidate genes from a large, genetically defined region. Candidate gene isolation by hybrid selection, genomic sequencing, and direct cDNA library screening identified 45 candidate gene fragments (CGFs) from a 600 kb genomic region that contains the BRCA1 gene. These CGFs define a minimum of 15 genes, six of which are newly localized to the BRCA1 region. We present an analysis of the efficiency and the sequences generated for each of these methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The high number of EST sequences found to map to the VAT1 gene suggest that it is an abundant message. Two of the ESTs map to the first intron of this gene (Harshman et al 1995 rpL21: A pseudogene of ribosomal protein L21 was identified in intron 13 of the BRCA1 gene (Figs. 1 and 6).…”
Section: Genome Research J 1039mentioning
confidence: 99%
See 3 more Smart Citations
“…The high number of EST sequences found to map to the VAT1 gene suggest that it is an abundant message. Two of the ESTs map to the first intron of this gene (Harshman et al 1995 rpL21: A pseudogene of ribosomal protein L21 was identified in intron 13 of the BRCA1 gene (Figs. 1 and 6).…”
Section: Genome Research J 1039mentioning
confidence: 99%
“…Two of the cDNA sequences (GenBank accession nos. U25789 and L38826) were identified in the search for BRCA1 and predicted to map to chromosome 17q12-21 (Albertsen et al 1994;Harshman et al 1995). U25789 was predicted to map between markers D17S1321 and D17S1325, a -600-kb region containing the BRCA1 gene .…”
Section: Genome Research J 1039mentioning
confidence: 99%
See 2 more Smart Citations
“…The most common approaches are (1) exon amplification (Buckler et al, 1991), (2) hybrid selection (Parimoo et al, 1991;Lovett et al, 1991), (3) analysis of genome sequence (UnerBacher and Mural, 1991), and (4) direct cDNA library screening . The advantages and disadvantages of these methods have been described (Hochgeschwender, 1992;Harshman et al, 1995). As it is unlikely that a single method will identify all the transcripts within a given genomic interval (Harshman et al, 1995), we sought to develop a detailed transcription map of the BRCA2 region by employing the first three of these techniques.…”
Section: Introductionmentioning
confidence: 99%